TOKOH UTAMA PADA FILM AASHIQUI 2 DALAM MEMBANGUN STRUKTUR DRAMATIK - Yanuar Rendika Ali Syahbana; Didik Suharijadi; Dwi Haryanto (Program Studi Film dan Televisi Universitas Jember, 2018)
Aashiqui 2 is the romantic musical drama in which the main focus is on the scene that produced by the main character. Through the main character, this film is created by using an interesting plot that builds a strong unity of dramatical structure. By this reason, the topic then is used as the background of the study by investigating a film entitled Aashiqui 2. The problem of the study focuses on how the main character constructs the dramatical structure. Through that focus, the goal of the study is to know how the role of the main character in constructing dramatical structure on Aashiqui 2. The analysis uses the Dramatic Plot Kernodle in classifying language that used by the main character. Afterwards, the analysis method uses mise-en-scene approach in investigating the main character that is relates to the elements of dramatical structure. In accoredance with visual data, the researcher uses one of cinemathography aspects called framming as the guidance in every step of analyzing the data. This study is qualitative research method by description formation. The technique of collecting data uses an observation, literature review and documentation. Based on the process of analysis, the result is to reveal how the main character’s role in constructing the dramatical structure on Aashiqui 2.